ROSS HARVEY, Digital Curation: A How-To-Do-It Manual - Matienzo, Mark A. (Archivaria, 2012)
Digital Curation: A How-To-Do-It Manual. ROSS HARVEY. New York: Neal-Schuman, 2010. xxii, 225 p. ISBN 978-1-55570-694-4.